MP001: Low acuity emergency department access: are other options available?. (2nd June 2016) - MacKay, J.; Atkinson, P.R.; Howlett, M.; Palmer, E.; Fraser, J.; Vaillancourt, E.
Abstract : Introduction: Patients with low-acuity (CTAS level IV and V) complaints often use the emergency department (ED) to access care. This has often been attributed to lack of a primary care (PC) provider. However, simply being registered with a primary care practitioner may not prevent low acuity ED presentation. There is some evidence that a lack of timely access to primary care may contribute to low acuity ED presentations. The Wait Time Alliance, a group of Canadian physicians and their respective professional associations, has recently set a benchmark of same day access to family doctors. It is unclear if this benchmark has been achieved in all jurisdictions.Methods: We performed linked cross sectional surveys to quantify the number of people presenting to a tertiary hospital ED (with 56, 000 annual visits) with non-urgent problems who felt unable to access PC. PC practices were also surveyed to assess access using the metric of time to third next available appointment. Sample size calculations were completed. Descriptive statistics were reported.Results: In the patient survey, 381 of 580 patients consented to participate. Of those, 89 patients met eligibility criteria. 32 (35.9%) reported that the wait to see their PC provider was "too long". 45 (50.5%) patients did not contact their PC office prior to ED presentation. 46 of 72 PC physician surveys were returned; a response rate of 63.8%. The mean time to third next available appointment in the region was 7.7 (95% CI 4.9-10.5) days (median 5 days, range 0-50 days).Conclusion: Fifty percent of low acuity patients did not attempt to access their PC provider prior to ED presentation. The benchmark of same day access to primary care has not been achieved in many practices in this region. Initiatives to promote primary care access would benefit both patients and providers.